Pengelolaan Pembelajaran Melalui Blanded Learning Dalam Meningkatkan Receptive Skill Peserta Didik di Pondok Pesantren - Hayati, Nur; Wijaya, Muallim (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Palapa Nusantara Lombok NTB, 2018)
This study discusses the management of learning through blanded learning in improving receptive skill of students in boarding school Bahrul Ulum Besuk Kidul, Besuk, Probolinggo. Arabic is now widely provided by using varied models and online learning media. However, the various learning models are still less relevant and efficient, which causes students to understand less ability receptive skill, especially on learning Arabic. The rapid development of information technology has provided a great opportunity for the development of online learning model on motivation or increase student learning interest. This study aims to produce a blended learning model, which is a combination of online learning model and face to face learning, which can improve the receptive skills of learners.